2005
DOI: 10.1007/s00418-005-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic signaling proteins: possible participation in the regulation of vasopressin and catecholamines biosynthesis in the hypothalamus

Abstract: The role of apoptotic signaling proteins for long-lived neurons in the mature brain is poorly understood. Recently, we have shown that water deprivation leads to the activation of vasopressin (VP) secretion and expression of Bcl-2 and caspase-9 apototic proteins in the hypothalamus of the rat brain. In the present work, we continued to study a possible relationship between the functional activity of neurosecretory cells of the hypothalamus and apoptosis related proteins. We found that water deprivation leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…It can activate mitochondrial caspases, which cleave MAP kinases (activators of CDC2 kinases and cell cycle at G2/M phase; Marchetti et al 2004) and induce apoptosis-related events (Braithwaite et al 2006, Chowdhury et al 2006. When concerned with the role of p53 in controlling secretory activity, it is able to suppress growth factor secretion (VEGF, Hassan et al 2006) and insulin-like growth factor binding proteins (Grimberg et al 2006), and to promote vasopressin and catecholamine secretion (Chernigovskaya et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It can activate mitochondrial caspases, which cleave MAP kinases (activators of CDC2 kinases and cell cycle at G2/M phase; Marchetti et al 2004) and induce apoptosis-related events (Braithwaite et al 2006, Chowdhury et al 2006. When concerned with the role of p53 in controlling secretory activity, it is able to suppress growth factor secretion (VEGF, Hassan et al 2006) and insulin-like growth factor binding proteins (Grimberg et al 2006), and to promote vasopressin and catecholamine secretion (Chernigovskaya et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, p53 plays an important functional role in the regulation of cell processes that are not connected with apoptosis. Previously, we had demonstrated that water deprivation leads to simultaneous activation of synthesis of VP and p53 in the mouse brain [6]. Moreover, p53 deficiency led to reduced expression of VP in the hypothalamic centers [6].…”
Section: Discussionmentioning
confidence: 98%
“…Dehydration, well known stimuli for vasopressin (VP) activation, also resulted in the increased expression of p53 protein in hypothalamic neurons [4,6]. Conversely, in p53-deficient mice the content of VP was significantly decreased in magnocellular neurons of the PVN and supraoptical nucleus (SON) of the hypothalamus [6], suggesting that p53 can participate in the regulation of VP expression.…”
mentioning
confidence: 99%
“…By reducing the gC1qR mitochondrial protein with an iRNA approach, the antiapoptotic property of the protein in the germ cells could be demonstrated. Chernigovskaya et al (2005) investigated the possible relationship between the functional activity of neurosecretory cells of the mouse hypothalamus and apoptosis related proteins. Their data suggest that p53, p21 (Waf1/Cip1) and Bcl-2 proteins, besides aVecting cell cycle, tumor suppression and apoptosis, may act as modulators of neurosecretory activity of hypothalamic neurons.…”
Section: Programmed Cell Death In Its Various Formsmentioning
confidence: 99%